2008
DOI: 10.1111/j.1755-148x.2007.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Notch1 and Notch2 contribute to the regulation of melanocyte homeostasis

Abstract: Notch signaling affects a variety of mammalian stem cells, but there has been limited evidence that a specific Notch molecule regulates adult stem cells. Recently, it was reported that the reduced Notch signaling initiated at the embryonic stage results in a gradual hair graying phenotype after birth. Here we demonstrate that the oral administration of a gamma-secretase inhibitor (GSI) to wild-type adult C57/Bl6 mice led to a gradual increase in gray spots, which remained unchanged for at least 20 weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 33 publications
(47 reference statements)
2
74
1
1
Order By: Relevance
“…Loss of Notch1 and Notch2 in mice results in abnormal pigmentation; these and other studies suggest that mutations in POGLUT1 resulting in aberrations in Notch signalling would lead to abnormal pigmentation and keratinocyte morphology 9, 10…”
mentioning
confidence: 83%
“…Loss of Notch1 and Notch2 in mice results in abnormal pigmentation; these and other studies suggest that mutations in POGLUT1 resulting in aberrations in Notch signalling would lead to abnormal pigmentation and keratinocyte morphology 9, 10…”
mentioning
confidence: 83%
“…In contrast to other organs, the implication of the Notch signaling pathway has only been recently addressed in the pigmentary system (Schouwey and Beermann, 2008), and mouse and human melanocytes have been shown to express members of this signal transduction pathway (Hoek et al, 2004;Haass and Herlyn, 2005;Moriyama et al, 2006;Nishikawa and Osawa, 2007). In vivo analyses have revealed that disruption of the Notch pathway in the melanocyte lineage, by either deleting Notch1 and Notch2 receptors (Schouwey et al, 2007;Kumano et al, 2008), or the transcription factor RBP-Jk (Moriyama et al, 2006;Aubin-Houzelstein et al, 2008), results in a precocious hair graying caused by the progressive loss of the melanocyte population. Hence, RBP-Jk-dependent Notch signaling (Schouwey et al, 2010) is required for maintenance of melanoblasts and melanocyte stem cells, and thus to ensure proper hair pigmentation in mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Subchronic dosing of GSIs can cause adverse effects in the gastrointestinal (GI) tract, thymus, spleen, skin, and hair in animals, likely resulting from reduced Notch signaling (Milano et al, 2004;Wong et al, 2004;Prasad et al, 2007;Kumano et al, 2008). In the GI tract, GSIs can cause decreased enterocyte differentiation, goblet cell metaplasia, and potential injury to the intestinal epithelium (Milano et al, 2004;Wong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%